Desempenho estratégico na gestão hospitalar: análise multicritério para suporte ao balanced scorecard - Lourenço, Angélica Terezinha Trentin (2016)
This study aimed to develop a model for performance measurement in hospital management through key indicators, unfold into good practices listed in the Balanced Scorecard perspectives aiming to outline the organizational strategic focus. After the definition of best practices, designed to valuation of ideal performance expected and diagnosed to held, providing opportunities for the development of a development index which was subjected to the method of supporting multi-criteria decision ELECTRE II, resulting in order to detect and prioritization of vulnerable alternatives. Through literature, if allowed to evidence that a significant amount of work converges to indicate how effective the use of BSC ally methods of supporting multi-criteria decision being checked 43 key performance indicators commonly used. Of these, 15 were chosen and deployed in 57 good practices taken by sub-indicators for the application of hospital performance measurement method. The results of the proposed method proved to be satisfactory because steering plenty of critical points that need to be better developed in the organization, and support decision-making processes and be in accordance with the mission, vision and values of the organization studied.